The competitive intelligence consultancy – a new information resource for decision making in the business sector: the case of Spain - Muñoz-Cañavate, Antonio; Herrera-Barragán, Marta; Hípola, Pedro (Journal of Business and Finance Librarianship, 2020)
The globalization of the economy has meant that firms increasingly need a great variety of information, which may be about its competitors, suppliers, distributors, potential customers, but also about technological, legal, sociological, about access to markets, etc. That information may refer to a single country or many. The Internet has led to the multiplication of business information resources, but, with the huge quantity of open access information resources being joined to the electronic information industry, retrieval of that information and endowing it with added value requires highly qualified personnel. Corporate librarians cannot always fulfill that function. That is why Competitive Intelligence consulting firms are beginning to proliferate worldwide since they provide a fundamental point of support for firms to be able to deal with all this information. By means of prior analyses, these firms generate “ad hoc” informative products for their corporate clients. The present work is an exhaustive description of this sector in Spain – its size, forms of operation, services offered, and sectors to which they are directed. This description may serve to help business librarians, brokers, and managers know whom they can turn to in their countries to resolve an informational problem whose complexity they can not address without external assistance.
Keywords: competitive intelligence; consultancy; information resources; support for company library; Spain; Scopus; Emerging